The FTIR Test and Behavior Mechanical Concrete with Pozzolan Substitution - Aulia, Teuku Budi; Fachruddin, Fachruddin; Husin, Husni; Hasan, Muttaqin; Samsunan, Samsunan; Tripoli, Bambang; Yusra, Andi (Applied mechanics and materials, 2024)
Pozzolan is a material that increases the strength of concrete. The pozzolan used in this study is mussel shell powder. The purpose of this study was to find out how MSP substitution affects concrete strength. Mussel shell powder (MSP) contains important levels of calcium oxide and silicon oxide (SiO2) and used as an alternative to Portland cement (PC) to reduce the amount of PC needed to make concrete will perform. The concrete designed according to the Standard Indonesian Method (SNI) and the slump should be between 75mm and 100mm. As a prototype, he built a concrete cylinder measuring 15 cm x 30 cm. The percentage changes when replacing PC with MSP were 0%, 2%, 4%, 6%, and 8%, respectively, with 0% substitute used as the control mixture. The samples evaluated for compressive and tensile strength after 7 and 28 days, respectively. As a result, in terms of compressive strength, the best replacement level for 28-day-old concrete is 6%, with a strength value of 32.46MPa. This resulted in a 21.98% increase in force compared to control. In contrast, replacing 2% PC with MSP achieved the highest shear strength after 28 days, with a strength value of about 2.584MPa, 10.48% higher than witnessed. The two samples all have slightly different chemical group bonds O-H, CH2, and C-H. The absorption range of the chemical bond of alkene is 1638.21cm-1, and group functional C=O of shell concrete of 1638.21cm-1. The group functional of C=O in the sample, but there is no functional group C in the shell.